FACTORS INFLUENCING THE INTENTION TO DONATE ON THE CROWDFUNDING PLATFORM: A CASE STUDY OF KITABISA.COM - Adam, Mochammad Riyadh Rizky; Arihta, Jocelyn (AKSELERASI: Jurnal Ilmiah Nasional, 2024)
Kitabisa.com has successfully established itself as one of the largest crowdfunding platforms in Indonesia. The goal of this study is to determine what motivational factors influence future generations' intentions to donate to Kitabisa.com. After conducting a thorough relevant literature review, various variables were predicted. They are empathy/altruism, gotong royong (mutual cooperation/community self-help) culture, brand trust, operational transparency, perceived ease of use, and religiosity. This study used a quantitative technique, with online surveys of Kitabisa.com donors. Purposive sampling was used to acquire data from 280 Kitabisa.com donors. The data were analyzed using multiple regression to assess two or more independent variables. The study's findings revealed that variables such as empathy/altruism, gotong-royong (mutual cooperation/community self-help) culture, brand trust, operational transparency, perceived ease of use, and religiosity all had an impact on donation intention. Furthermore, this study will look at what variables influence future generations' motivation to donate in the future, as well as how Kitabisa.com can better understand their behavior.